RIVER DEBRIS TRANSPORT PLANNING FROM SOURCE TO PUTRI CAMPO FINAL PROCESSING PLACE, SURAKARTA CITY - Sari, Mega Mutiara; Inoue, Takanobu; Harryes, Regil Kentaurus; Yokota, Kuriko; Septiariva, Iva Yenis; Suhardono, Sapta; Kato, Shigeru; Notodarmojo, Suprihanto; Nafisah, Aninda Putri; Suryawan, I Wayan Koko (Diponegoro University, 2022)
The waste from the river is one of the obstacles in managing the Bengawan Solo River, Surakarta City. River debris is usually collected in tributaries so as not to carry the pollutant load to the watershed, causing flooding, and then transported to the Final Processing Site (TPA). This study aims to analyze the waste transportation system from the source to the landfill. This research was conducted by direct observation and using Multi-Attribute Utility Theory (MAUT) for determination. Alternative waste transportation used are haul container system (HCS) and stationary container system (SCS). The criteria used are the number of ritations, price, ease of transportation, potential damage, maintenance, and type of container. Based on the weighting results on the MAUT analysis, transportation with the SCS method has a higher weight than the HCS method.